Developing a Storytelling Framework for Leadership (International Journal of Food and Nutritional Sciences, 2022)
Storytelling is a very old concept of developing culture. Storytelling as a method has more emotional connect with people. Stories also have much more retention as compared to a report of general information. Hence this research paper explores to understand the use of storytelling by leaders of the organization. This being exploratory research, in depth interviews of 27 corporate leaders was conducted, to understand how they use storytelling. The interviews suggest various benefits of using storytelling methods including motivating employees, reducing conflicts, leadership development, team work, establishing organizational culture and so on. The research suggests that storytelling is used widely by the leaders, though it is not an organized process. Hence a framework of storytelling is suggested in the article.